Re-engineering Eclipse MDT/OCL for Xtext - Willink, Edward (Electronic Communications of the EASST, 2011)
The current tooling used for the Eclipse OCL project uses an LALR parser generator. Enhancing the tooling to support editing motivated a migration to exploit the inherently model-driven characteristics of Xtext. This paper summarizes the experiences of that migration, identifies the many benefits and discusses a few changes in implementation approach that were required. Objective performance and size comparisons between the old LALR and new Xtext approach are provided.